TEACHER’S LEADERSHIP TEACHING STRATEGY SUPPORTING STUDENT LEARNING DURING THE COVID-19 DISRUPTION - Aslan Aslan; Silvia Silvia; Budi Sulistiyo Nugroho; M Ramli; Rusiadi Rusiadi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This project aimed to review teacher’s leadership learning strategies in improving student learning outcomes since the government sent students home to slow the spread of the COVID-19 pandemic. The student’s learning success during a pandemic is closely related to understanding and implementing teacher leadership strategies in helping students learn from home. To support teachers in student learning success, we have reviewed literature, especially student learning during school closings. After data collection, we continued in-depth analysis and interpretation with a descriptive qualitative approach. Analysis and interpretation include the competencies to be achieved, learning motivation, teaching materials, mentoring methods, and success evaluation rubrics. After we connected all the elements above with teaching, pedagogy, and understanding of the realities of student learning during the pandemic, we finally succeeded in compiling a strategic formulation of the teacher leadership strategies as follows: 1) spatial learning practice, 2) retrospective approach, 3) practical elaborative learning, 4) collaborative learning, 5) interleaving approach, 6) concrete commitment, 7) multiple coding skills, 8) helpful resources, 9) digital competence, and 10) celebrating every success. These findings are they are valid and reliable. Therefore, the implication of this findings can be a strategy for teachers to back up students learning from home today where teaching still remains in remote settings.